HUBUNGAN PERSEPSI SISWA TENTANG MATA PELAJARAN SEJARAH TERHADAP HASIL BELAJAR SEJARAH DI SMAN 6 MANDAU KECAMATAN MANDAU KABUPATEN BENGKALIS - Rezky Aditiya; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the relationship between students' perceptions of historical subjects with the results of the study at SMAN 6 Mandau, Mandau District, Bengkalis Regency. Data were collected from 31 students of class XII IPS, using the random sampling method. For student perception variables, measured using a questionnaire distributed to 31 students of class XII IPS who were selected as research respondents. While the learning outcome variables are found through the odd semester exam scores for the 2018/2019 Academic Year obtained from teachers in the field of historical studies at SMAN 6 Mandau. The data analysis technique uses the Product Moment correlation analysis. Correlation test results obtained the correlation coefficient of perception of students with historical learning outcomes, r count = 0.126 and r table = 0.300 which means r count = 0.126 ≤ r table = 0.300 so that the conclusions H0 are accepted and Ha is rejected, and the correlation direction is positive, while the correlation category is very low. Then the coefficient of determination (r2) is = 0.015. This means that students 'perceptions of history lessons contribute 1.5% to historical learning outcomes and the remaining 98.5% are factors beyond students' perceptions of history lessons. The results of this study state that there is no significant positive relationship between the perceptions of students with historical learning outcomes at SMAN 6 Mandau, Mandau District, Bengkalis Regency. The good and bad perceptions of students about historical subjects have nothing to do with high and low historical learning outcomes.Key Words: Student Perception, Historical Lessons, Historical Learning Outcomes